МУТАЦІЇ В НЕКОДУЮЧИХ ДІЛЯНКАХ ГЕНОМУ КЛІТИН, ЩО ПОРУШУЮТЬ ЗВ’ЯЗУВАННЯ З ТРАНСКРИПЦІЙНИМ ФАКТОРОМ HNF4Α, ВПЛИВАЮТЬ НА АКТИВНІСТЬ ЕНХАНСЕРІВ ГЕНІВ, ЯКІ АСОЦІЙОВАНІ З ПРОГРЕСУВАННЯМ РАКУ ПЕЧІНКИ - Cavalli, M.; Diamanti, K.; Pan, G.; Dabrowski, M.J.; Komorowski, J.; Wadelius, C. (PH Akademperiodyka, 2023)
Background: Somatic mutations in coding regions of the genome may result in non-functional proteins that can lead to cancer or other diseases, however cancer mutations in the non-coding regions have rarely been studied and the interpretation of their effects is difficult. Non-coding mutations might act by breaking or creating transcription factor binding motifs in promoters, enhancers or silencers resulting in altered expression of target gene(s). A high number of mutations have been reported in coding and non-coding regions in cells of liver cancer. Hepatocyte nuclear factor 4α is a transcription factor that regulates the expression of several genes in liver cells, while the motifs it binds are frequently mutated in promoters and enhancers in liver cancer. Aim: The aim of the study is to evaluate the genetic effects of a non-coding somatic mutation frequently observed in liver cancer. Materials and Methods: We evaluated experimentally the effects of a somatic mutation frequently reported in liver cancer as a motif-breaker for the binding of hepatocyte nuclear factor 4α. The effects of the mutation on protein binding and enhancer activity were studied in HepG2 cells via electrophoresis mobility shift assay and dual luciferase reporter assays. We also studied genome-wide promoter-enhancer interactions performing targeted chromosome conformation capture in liver tissue to identify putative target genes whose expression could be altered by the mutation. Results: We found that the mutation leads to reduced protein binding and a decrease in enhancer activity. The enhancer harboring the mutation interacts with the promoters of ANAPC13, MAP6D1 and MUC13, which have been implicated in liver cancer. Conclusions: The study highlights the importance of non-coding somatic mutations, vastly understudied, but likely to contribute to cancer development and progression.